PENDAMPINGAN PROGRESIF JACOBSON TERHADAP TEKANAN DARAH DAN KECEMASAN PASIEN HIPERTENSI DI RS SITI KHODIJAH - Yumni, Fathiya Luthfil; Kholidah, Nurilla (PPM STIKES Adi Husada, 2023)
Introduction & Aim: Hypertension is one of the most deadly diseases in the world called the silent killer disease. If hypertension is not handled properly, it will lead to degenerative complications such as kidney failure, myocardial infarction, and stroke. These causes anxiety. The anxiety will make the heart pumps the blood throughout the whole body with high pressure hence the blood pressure will not be easily lowered. Anxiety is a psychological disorder that is frequently experienced by patients with hypertension. The aim of this community service was to explain the effect of Progressive Jacobson therapy to lower the blood pressure and anxiety of patients with hypertension. Method of Activity: The community service used in this community service is from education and guidance inwards Shofa Marwah Siti Khadijah Hospital Surabaya. This plan will show the difference between before and after giving Progressive Jacobson therapy. There are twelve male patients with grade 2 hypertension who felt anxiety. The measurement was done using a sphygmomanometer and DASS 42 (Depression Anxiety Stress Scale) questionnaire. Results: The result showed that respondents undergo increased blood pressure and anxiety before receiving Progressive Jacobson therapy. After being treated by the Progressive Jacobson Therapy, respondents felt more relaxed. The level of anxiety was decreased to a mild level and the blood pressure was lowered to Grade 1. Discussion: Patients with hypertension in room Shofa Marwah Siti Khadijah Hospital Sidoarjo using Progressive Jacobson Therapy resulted in lowered blood pressure and anxiety level.